LEADERSHIP OF THE PROPHET MUHAMMAD - ANISA, RESTI; MUHAMMAD NUR’AIN; NADIA RAPINAH; NOR SYIFA (Educational Leadership: Jurnal Manajemen Pendidikan, 2023)
In this research, the authors used a qualitative research method with a library research and used descriptive analysis data analysis techniques. With the aim of research to find out leadership in upholding religion and taking care of matters that exist in the world more deeply. The results of the research are that in an organization or social organization, a leader is needed to manage various things in society. For example, in the small world, the leader is in the family circle. The family certainly has a leader who directs the goals to be achieved in the family. Leadership is a person's attempt to influence the behavior of a person or group. Companies influence this behavior to achieve individual or group goals. There are many theories of leadership, including trait theory, environmental theory, behavioral theory, situational theory, and charismatic theory. A leader must have every leadership style in accordance with the personality and goals to be achieved. The leader's character certainly affects the results of the goals achieved in the organization. Management is a very important factor that affects organizational performance, because management is the main activity to achieve organizational goals. The leadership of the Prophet Muhammad SAW set an example for leaders to prioritize the interests of the people, teach and practice good morals, have a clear vision, and be fair.